2002
DOI: 10.1111/j.1471-0528.2002.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin A deficiency during pregnancy on maternal and child health

Abstract: The study suggests that subclinical vitamin A deficiency is a problem during the third trimester of pregnancy. Serum concentration of retinol <20 microg/dL appears to indicate a deficient status, and is associated with an increased risk of preterm delivery and maternal anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…Because maternal tissues are progressively depleted of vitamin A to supply fetal demands [14], women who initially possess marginal or even adequate vitamin A stores at the beginning of pregnancy are at an increased risk of vitamin A inadequacy as pregnancy progresses. Radhika et al found a significantly increased risk of spontaneous preterm delivery, maternal anemia, and pregnancy-induced hypertension when retinol levels were below 0.70 µmol/L, and based on those functional effects recommend a level of 0.70 µmol/L to define vitamin A deficiency in pregnancy [3]. Measurements of vitamin A concentrations in breast milk, maternal serum vitamin A concentration, and maternal dietary intake suggest that a maternal concentration of ≥1.05 µmol/L is necessary in order to maintain a sufficient vitamin A content in breast milk [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because maternal tissues are progressively depleted of vitamin A to supply fetal demands [14], women who initially possess marginal or even adequate vitamin A stores at the beginning of pregnancy are at an increased risk of vitamin A inadequacy as pregnancy progresses. Radhika et al found a significantly increased risk of spontaneous preterm delivery, maternal anemia, and pregnancy-induced hypertension when retinol levels were below 0.70 µmol/L, and based on those functional effects recommend a level of 0.70 µmol/L to define vitamin A deficiency in pregnancy [3]. Measurements of vitamin A concentrations in breast milk, maternal serum vitamin A concentration, and maternal dietary intake suggest that a maternal concentration of ≥1.05 µmol/L is necessary in order to maintain a sufficient vitamin A content in breast milk [26].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate vitamin A status in the mother is critical for fetal growth, morphogenesis, and maturation of multiple organ systems, including the immune system, lungs, and eyes [1,2]. Maternal vitamin A deficiency increases the risk of complications during pregnancy and in the postpartum period and has been positively associated with preterm delivery [3], maternal infections, night blindness, anemia [4], and birth defects [5]. Maternal vitamin A deficiency also has serious repercussions for the newborn and is associated with depressed immune function and higher morbidity and mortality due to infections [1], low birth weight [6], diaphragmatic hernia [7], bronchopulmonary dysplasia and other respiratory disease [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that excess or lack of RA during early embryogenesis causes malformations [51,52], through mispatterning of the embryonic tissue layers and the anterior-posterior body axis. Several RAR knockout mice have been created [53].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, more than half of women out of 200 have a low rate of retinol, and 18.5% of them are deficient in Vitamin A [8]. In India, Radhika et al found that 27% of women have Vitamin A deficiency in a population of 736 pregnant women [11]. In Egypt, in a study of a population of 80 mother-child pairs, 20% of mothers had Vitamin A deficiency and a significant difference between mean retinol of newborns from deficient mothers and those from non-deficient mothers [12].…”
Section: Discussionmentioning
confidence: 99%